Peran Pemerintah dalam Penerapan Smart Branding di Kabupaten Blora - Sofie, Tria; Rachmawati, Rini (Jurnal Bina Praja, 2024)
Blora Regency is one of the districts selected in the "Movement Towards 100 Smart Cities" program, where smart branding is one of the important elements that support the implementation of smart cities in the district. Smart branding utilizes local potential and uniqueness to promote regions' competitiveness. The application of smart branding is seen in three aspects: tourism branding, business branding, and city appearance branding. This research analyzes the condition of smart branding in Blora Regency and the government's role in supporting smart branding. It will also analyze short-, medium-, and long-term smart branding priority programs. The research used a qualitative method, where data collection was conducted through observation, in-depth interviews, and documentation. This research shows that smart branding in Blora Regency is one of the efforts to increase promotion and create a competitive area. This condition encourages tourists to visit and investors to invest their capital. Strengthening smart branding is also carried out through city planning. Meanwhile, accessibility optimization continues. Some slogans strengthen smart branding, including "Dolan Blora." The government's role is quite good in providing training and assistance for tourism managers, promoting the area to investors, and increasing accessibility. Various programs are deployed to support smart branding in the short, medium, and long term. Several programs to support the implementation of smart branding have been implemented either by the government or by involving third parties.